Continuous video recording with simultaneous amplitude-integrated EEG monitoring to improve seizure recognition in newborns - Kage, Anup; Santana, Yesenia C.; Malcolm, Ivone L.; Francia, Caroline; Yoong, Michael; Wertheim, David; Shah, Divyen (Frontiers in Pediatrics, 2025)
IntroductionSeizures in newborn infants are considered a neurological emergency requiring prompt treatment to limit exacerbation of brain injury. Digital monitors incorporating limited channel raw EEG and amplitude-integrated EEG (aEEG/EEG) are widely used. This study aimed to determine if continuous video recording with simultaneous aEEG/EEG recording enhances seizure recognition.MethodsNewborns at risk of seizures who underwent neuromonitoring with aEEG/EEG were prospectively recruited to an observational study in a tertiary neonatal centre. Video recordings were commenced after obtaining written consent from parents.ResultsSimultaneous video recordings with aEEG/EEG were obtained in 15/47 newborns recruited to study. A total of 116 electrographic seizure episodes were detected on aEEG/EEG when a total of 56 episodes of abnormal movements were noted on video recordings. Only 8 of these abnormal movements had simultaneous electrographic seizures on aEEG.ConclusionUse of simultaneous video and aEEG/EEG recordings in newborns at risk of seizures is feasible. It not only assists confirmation of the presence of seizures but may also help in identifying movements associated with abnormal neurology that are not seizures.